Pelatihan Sablon Digital Transfer Film (DTF) dan Digital Marketing Untuk Meningkatkan Produktivitas Ekonomi Kelompok Remaja Masjid Jamiul Ihsan - Lalu Mutawalli; Hairul Fahmi; Hasyim Asyari (Jurnal Pengabdian Masyarakat, 2025)
This community service program focuses on empowering the Youth of Jamiul Ihsan Mosque in Rumak Village, West Lombok, to address their limitations in productive skills and minimal understanding of the creative economy. This initiative is motivated by the village's potential in the craft sector, which has not been optimally developed, especially in terms of digital marketing. The solution offered is integrated training in Digital Transfer Film (DTF) screen printing technology and digital marketing. The goal is to transform the role of the mosque youth from managing religious activities into independent creative entrepreneurs, while also unlocking the potential for establishing mosque-based MSMEs (Micro, Small, and Medium Enterprises) to support financial independence. The implementation method consists of six continuous stages: Socialization (FGD), Planning, Training, Mentoring, Evaluation, and Development. Technical training includes mastering DTF screen printing tools, graphic design (CorelDRAW and Photoshop), production, and quality control. Non-technical training focuses on digital marketing strategies through Instagram and Facebook, including content creation, copywriting, and analytics. Evaluation through pre-test and post-test showed a significant increase in participants' understanding by 21.6%, with the highest surge in digital marketing material (34%). These results prove the effectiveness of the participatory and integrated training approach in enhancing the capacity of the mosque youth, thereby paving the way for the creation of a sustainable screen-printing business that contributes to local economic growth.